2013
DOI: 10.1210/en.2013-1051
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Splicing Regulator Protein 1 and Alternative Splicing in Somatotroph Adenomas

Abstract: Somatotroph adenomas secrete supraphysiological amounts of GH, causing acromegaly. We have previously hypothesized that epithelial mesenchymal transition (EMT) may play a central role in the progression of these adenomas and that epithelial splicing regulator 1 (ESRP1) may function prominently as a master regulator of the EMT process in pituitary adenomas causing acromegaly. To further elucidate the role of ESRP1 in somatotroph adenomas and in EMT progression, we used RNA sequencing (RNAseq) to sequence somato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Epithelial splicing regulatory protein 1 (ESRP1), also named as RNA-binding motif protein 35A (RBM35A), is a critical elements in the human cancer epithelial mesenchymal transformation (EMT) [15][16][17][18]. It has been identified that ESRP1 regulate the alternative splicing events associated with epithelial phenotypes in OSCC [19].…”
Section: Corrected: Correctionmentioning
confidence: 99%
“…Epithelial splicing regulatory protein 1 (ESRP1), also named as RNA-binding motif protein 35A (RBM35A), is a critical elements in the human cancer epithelial mesenchymal transformation (EMT) [15][16][17][18]. It has been identified that ESRP1 regulate the alternative splicing events associated with epithelial phenotypes in OSCC [19].…”
Section: Corrected: Correctionmentioning
confidence: 99%
“…Gene expression profiling and proteomics studies [3846] led to the identification of genes associated with invasion and aggressive behavior [42, 47]. Changes in EMT markers have been seen in sporadic somatotroph adenomas with lower E-cadherin and ESRP1 expression [34, 48, 49]. Loss of ESRP1 in ~90% of AIP pos cases indicates that ESRP1 may be an important regulator of tumor invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of ESRP1 induces EMT phenotypes (Reinke et al, 2012; Warzecha et al, 2009). Very recently, ESRP1 was identified as a master regulator of EMT in human GH-secreting adenomas (Lekva et al, 2012, 2013). ESRP1 is positively correlated with E-cadherin expression in GH-secreting adenomas and its depletion by RNAi results in down regulation of E-cadherin in a GH-adenoma cell line (Lekva et al, 2012).…”
Section: The Rb Connectionmentioning
confidence: 99%